Methodological Foundations of Emotional Intelligence Development for Improving Intergenerational Communication - Arusiak Amarian (Emerging Frontiers Library for The American Journal of Social Science and Education Innovations, 2025)
This article examines the methodological foundations for developing emotional intelligence (EI) as a means to improve intergenerational communication. It reviews major theoretical models—including the Mayer-Salovey ability model, Goleman’s framework, and Bar-On’s competencies—and discusses how these theories apply to interactions between different age groups. The paper outlines psychological, educational, and sociocultural approaches to EI training, presenting evidence that targeted interventions (from workshops to mentoring programs) can enhance empathy, conflict resolution, and overall communication between generations. Practical applications in workplaces, educational settings, and community initiatives are discussed as viable strategies for bridging the generational gap and fostering mutual understanding.